2014
DOI: 10.3390/s140609984
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic miRNA Detection Using Cobalt Porphyrin-Modified Reduced Graphene Oxide

Abstract: Metalated porphyrins have been described to bind nucleic acids. Additionally, cobalt porphyrins present catalytic properties towards oxygen reduction. In this work, a carboxylic acid-functionalized cobalt porphyrin was physisorbed on reduced graphene oxide, then immobilized on glassy carbon electrodes. The carboxylic groups were used to covalently graft amino-terminated oligonucleotide probes which are complementary to a short microRNA target. It was shown that the catalytic oxygen electroreduction on cobalt p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In our study, the preparation of disposable CA‐GO‐PGEs was resulted only in 15 min. In this aspect, this approach was found less time‐consuming assay contrast to the earlier studies performed by glassy carbon electrodes , or screen‐printed gold electrode . Additionally, the detection of miRNA achieved in both buffer (PBS) and diluted FBS medium within 35 min respectively with a detection limit of 0.29 μg/mL (i.e, 41.2 nM), and 1.12 μg/mL (i.e., 159 nM).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the preparation of disposable CA‐GO‐PGEs was resulted only in 15 min. In this aspect, this approach was found less time‐consuming assay contrast to the earlier studies performed by glassy carbon electrodes , or screen‐printed gold electrode . Additionally, the detection of miRNA achieved in both buffer (PBS) and diluted FBS medium within 35 min respectively with a detection limit of 0.29 μg/mL (i.e, 41.2 nM), and 1.12 μg/mL (i.e., 159 nM).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to the previous reports, our proposed electrochemical biosensor platform presented some advantages; such as, easy-to-handle, cost-effective, fast, disposable electrode surface modification and portable. In this aspect, our biosensor provides a cost-effective assay in contrast to the earlier studies performed using screen-printed electrodes [ 41 ], or gold electrodes [ 42 ], AuNPs-modified electrodes [ 43 ] and some optical biosensor systems [ 44 ]. Additionally, the detection of miRNA achieved in both buffer (PBS) and diluted FBS medium within detection limits of 109 nM and 117 nM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, its rapid detection relies on classical techniques such as Northern blot, real-time quantitative reverse transcription PCR (qRT-PCR), or optical DNA chips based SPR or fluorescence labeling. De Souza et al reported a carboxylic acid functionalized cobalt porphyrin (CoTCPP, cobalt tetra­(4-carboxyphenyl) porphyrin)) noncovalently physisorbed (via π–π interactions) on reduced graphene oxide (Figure A) and then immobilized on a glassy carbon electrode . Further, the carboxylic groups were covalently grafted with amino-terminated oligonucleotide probes, complementary to a short microRNA target.…”
Section: Porphyrin and Graphene/carbon Nanotube Conjugatesmentioning
confidence: 99%